Rancang Bangun Website Sistem Informasi Pelaksanaan Skripsi Program Studi Broadband Multimedia - Dwiyanti, Diah; Frendiana, Viving (Politeknik Negeri Jakarta, 2023)
The utilization of information technology in various sectors has a significant impact on the management of every activity to support effectiveness and the quality of performance. The Broadband Multimedia Study Program need a website for bachelor thesis purpose. In the thesis proposal seminars and defenses, the grading process is done manually on a form, and then the examination committee re-enters and accumulates the data manually, which takes more time and is susceptible to data input errors. Therefore, a website has been created to assist students, examiners or supervisors, and the committee in the thesis process. This website uses MySQL as the database and CSS, HTML, and PHP as the interface. The website's testing is based on the ISO/IEC 25010 testing standard, covering aspects such as functional suitability, performance efficiency, reliability, security, usability, and portability. The results of the functional suitability test achieved a success rate of 100%, with an average page loading time of 1.59 seconds for performance efficiency. Reliability scored 100% and met Telcordia standards. Security showed low vulnerability, usability received a score of 89.46%, indicating it is very good, and the portability test was conducted on four different devices and ran smoothly. Keywords: ISO/IEC 25010, Information System, Thesis, Website